2012
DOI: 10.1185/03007995.2012.684675
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy: a new predictor in patients on regular hemodialysis

Abstract: Prevalence of DR is high among HD patients and associated with high mortality. DR is an independent predictor for PAD and not for transplantation. Early detection of DR is highly recommended among HD population for risk-stratification and counseling. Further randomized controlled studies are needed to support our finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
6
2
Order By: Relevance
“…The results of the multivariate analysis showed that the risk of foot ulceration was independently associated with DR and the presence of stenosing carotid plaques and that amputations were also independently associated with DR. The prevalence of DR among type 2 DM patients in haemodialysis has been previously reported to be between 70% and 79% [ 8 , 20 ], which is only slightly higher than the 63% observed in our study. This is in line with the results of a retrospective study where the incidence of retinopathy was found to be significantly higher among subjects in haemodialysis who had a foot ulcer than that among those who did not (88% versus 54%) [ 21 ] and also with a recent meta-analysis that identified retinopathy as a risk factor for foot ulceration in adults with ESRD treated with dialysis [ 22 ].…”
Section: Discussioncontrasting
confidence: 85%
“…The results of the multivariate analysis showed that the risk of foot ulceration was independently associated with DR and the presence of stenosing carotid plaques and that amputations were also independently associated with DR. The prevalence of DR among type 2 DM patients in haemodialysis has been previously reported to be between 70% and 79% [ 8 , 20 ], which is only slightly higher than the 63% observed in our study. This is in line with the results of a retrospective study where the incidence of retinopathy was found to be significantly higher among subjects in haemodialysis who had a foot ulcer than that among those who did not (88% versus 54%) [ 21 ] and also with a recent meta-analysis that identified retinopathy as a risk factor for foot ulceration in adults with ESRD treated with dialysis [ 22 ].…”
Section: Discussioncontrasting
confidence: 85%
“…Therefore, it is clearly seen that in many countries, the incidence of both DM and MVC is increasing exponentially which poses a great challenge for healthcare authorities and resources. [ 8 78 79 80 ]…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a recent study among patients with hemodialysis that found a significant correlation between diabetic retinopathy and peripheral arterial disease. 18 There are several limitations to this study. The study population was restricted to inpatients at UPMC Mercy Hospital in Pittsburgh, an inner city community teaching hospital.…”
Section: Stage N Prevalence (%)mentioning
confidence: 94%
“…10 After examining factors associated with diabetic retinopathy, duration of diabetes and history of renal disease were each found to be independently predictive of diabetic retinopathy in the inpatient population, which is consistent with previous studies. 17 18 Although microalbuminuria has been shown to be a risk factor for retinopathy in patients with type 1 diabetes but not type 2 Figure 1 Barriers to diabetic retinopathy screening examinations as reported by those patients who did not have dilated fundus examinations in the previous year. DR, diabetic retinopathy.…”
Section: Stage N Prevalence (%)mentioning
confidence: 99%